Preferensi Filantropi Perempuan pada Nasyiatul Aisyiyah di Jawa Timur - Ninik Annisa (JURNAL INDO-ISLAMIKA, 2012)
This article examines the preferences of the Nasyiatul Aisyiyah philanthropy that encourage the development of women empowerment. The Nasyiatul Aisyiyah is a female voluntary- and Islamic-based- organization, which was under the auspice of the Aisyiyah until 1965 when Muhammadiyah granted their autonomy. Since its first establishment, the Nasyiah has devoted itself to the development of philanthropy. In this article, I contend that the Nasyiah philanthropy has experienced up and down situation, although the Nasyiah philanthropy has developed significantly in its efforts to empower women in the community. The I find that the preferences of the Nasyiah philantrophy consist of self-actualization, women empowerment, social entrepreneurship, and social welfare.